Edukasi dan Pendampingan Paduan Suara Gereja bagi Remaja HKBP Judika Laguboti Kota - Lamsihar Simanungkalit (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service aims to enhance adolescents’ understanding and appreciation of choir ministry at HKBP Judika Resort Laguboti Kota. The program was implemented using educational approaches, including lectures and interactive discussions, alongside technical guidance covering vocal training, articulation, intonation, and harmonization. The primary objective was to cultivate awareness that the choir is not merely a singing group, but a form of spiritual ministry that facilitates congregational engagement in worship and supports the spiritual growth of its members. The intervention led to improvements in musical skills, teamwork, discipline, and participants’ liturgical and spiritual comprehension. Participants also recognized that each song functions as a vehicle for worship and faith-based service. Consequently, the program effectively highlighted the choir’s role as a meaningful instrument of worship, both musically and spiritually, while fostering adolescents’ sincere and responsible participation in church ministry.